The path to change: key factors to the new stage of Global Information and Communication Markets (Law, State and Telecommunications Review, 2010)
Peter F. Cowhey and Jonathan D. Aronson, with Donald Abelson. Transforming Global Information and Communication Markets: The Political Economy of Innovation. Cambridge: MIT Press, 2009, 341p. (R$82,62).